Penerapan Analisis Space Syntax pada Peningkatan Mitigasi Banjir Jakarta - Stepanus Andi Saputa (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
Flooding is an annual issue that continues to threaten the Special Capital Region of Jakarta, with significant impacts on infrastructure and the lives of its residents. Approximately 70% of Jakarta's area has been submerged during major floods, disrupting inter-regional access, causing casualties, and resulting in substantial economic losses. One of the primary causes of flooding is the growth of illegal settlements along riverbanks due to poorly organized spatial planning, leading to river narrowing and increased risk of overflow during heavy rainfall. Areas like Kampung Melayu along the Ciliwung River are particularly prone to annual flooding. The Provincial Government of the Special Capital Region of Jakarta has undertaken various mitigation programs, including river normalization, river naturalization, and the construction of infiltration wells. However, implementing these programs has often been suboptimal, with shifting policy priorities depending on leadership changes. Additionally, limited attention has been given to the road network as part of flood disaster mitigation, despite its crucial role in supporting evacuation and mobility during emergencies. This study aims to evaluate the vulnerability of road networks using the space syntax theory, which provides an in-depth analysis of spatial relationships. The method employed involves axial map analysis using Depthmap software to map spatial connections and the integration levels of road networks. The study compares the performance of road networks under normal conditions and during flooding. It also examines the performance of bridges and inter-regional connecting routes. The research focuses on areas along the Ciliwung River, particularly Kampung Melayu, covering a 3 km radius, one of 69 flood-affected regions. The study's findings are expected to provide strategic recommendations to improve the overall performance of road infrastructure, thereby enhancing the effectiveness and sustainability of flood mitigation efforts.